(untitled) (Bangladesh Journal of Zoology, 2015)
Brine salt curied (BS) Taki fish and the small Tengra fish were studied to observe such salting procedure on their bio-chemical composition stored at room temperature (26-320C). In fresh-processed condition, moisture, protein, fat, ash, pH and free fatty acid were 62.28%, 18.02%, 2.76%, 17.24%, 6.8 and 0.5% in BS taki fish and 57.35%, 15.3%, 6.84%, 20.8%, 5.9 and 0.9%, respectively in tengra. The value of moisture, pH and FFA increased significantly (p<0.05) with the time of storage and these values rapidly increased in cured taki than BS tengra and at the end of 75 days BS taki became spoiled whereas BS tengra still remained in fresh condition. It was observed that BS tengra fish-product had longer shelf life (120 days) and was found better for preservation in laboratory condition. This work also showed that the effect of the treatment on a fish sample dependent on the fish species. Bangladesh J. Zool. 42(2): 271-276, 2014